Hubungan Kepemimpinan dengan Upaya Pencegahan Hais Pada Masa Pandemi Covid 19 di Rumah Sakit Zainal Abidin Pagar Alam Way Kanan - King King; Dewi Kusumaningsih; M. Ricko Gunawan (Universitas Malahayati Lampung, 2024)
ABSTRACT Healthcare Associated Infections (HAIs) are a major problem faced by hospitals. HAIs are infections that are acquired and develop during hospitalization. One of the management functions is organizing, where the head of the room should develop an objective nursing organization so as to facilitate nurses in carrying out nursing care, especially infection prevention and control efforts. The purpose of this research is to know the relationship between leadership and efforts to prevent menstruation during the Covid 19 pandemic at Zainal Abidin Hospital Pagar Alam Way Kanan in 2021. This research is a quantitative research with a cross sectional approach. The population in this study were all health workers at Zainal Abidin Hospital Pagar Alam Way Kanan in 2021 as many as 164 people with a sample of 87 respondents using purposive sampling technique. This research was conducted at Zainal Abidin Hospital Pagar Alam Way Kanan in February-March 2021. Data collection used a questionnaire. Data analysis was univariate and bivariate (chi square). it is known that respondents with negative leadership are 17 (19.5%) and respondents with positive leadership are 70 (80.5%) and respondents with good menstruation prevention efforts are 44 (50.6%) and respondents with less menstrual bleeding prevention efforts good as many as 43 (49.4%). There is a relationship between leadership and efforts to prevent menstruation during the covid 19 pandemic at Zainal Abidin Hospital Pagar Alam Way Kanan in 2021 with a value (p-value = 0.003). Suggestion: for the hospital to be able to make efforts to prevent Healthcare Associated Infection (Hais) in accordance with the existing SOPs in order to avoid an increase in the incidence of nosocomial infections in hospitals, such as removing watches or jewelry when taking action, always wearing a mask and wearing gloves, apply hand washing. Keywords: Leadership and Healthcare Associated Infection (Hais), Covid-19 ABSTRAK Healthcare Associated Infections (HAIs) merupakan masalah besar yang dihadapi rumah sakit. HAIs adalah infeksi yang didapatkan dan berkembang selama pasien dirawat di rumah sakit. Salah satu fungsi manajemen adalah pengorganisasian, dimana kepala ruang hendaknya mengembangkan organisasi keperawatan secara objektif sehingga memudahkan perawat dalam melaksanakan asuhan keperawatan khususnya upaya pencegahan dan pengendalian infeksi. Tujuan penelitian ini diketahui hubungan kepemimpinan dengan upaya pencegahan Hais Pada Masa Pandemi Covid 19 Di Rumah Sakit Zainal Abidin Pagar Alam Way Kanan Tahun 2021. Penelitian ini merupakan penelitian kuantitatif dengan pendekatan Cross Sectional. Populasi dalam penelitian ini seluruh tenaga kesehatan di Rumah Sakit Zainal Abidin Pagar Alam Way Kanan tahun 2021 sebanyak 164 orang dengan sampel yang digunakan sebanyak 87 responden menggunakan teknik purposive sampling. Penelitian ini telah dilakukan di Rumah Sakit Zainal Abidin Pagar Alam Way Kanan pada Februari-Maret 2021. Pengumpulan data menggunakan kuesioner. Analisis data secara univariat dan bivariat (chi square). Diketahui responden dengan kepemimpinan negatif sebanyak 17 (19,5%) dan responden dengan kepemimpinan positif sebanyak 70 (80,5%) dan responden dengan upaya pencegahan hais baik sebanyak 44 (50,6%) dan responden dengan upaya pencegahan hais kurang baik sebanyak 43 (49,4%). Ada hubungan kepemimpinan dengan upaya pencegahan hais pada masa pandemi covid 19 di Rumah Sakit Zainal Abidin Pagar Alam Way Kanan tahun 2021 dengan nilai (p-value = 0,003). Saran : bagi pihak rumah sakit agar dapat melakukan upaya pencegahan Healthcare Associated Infection (Hais) sesuai dengan SOP yang ada guna menghindari peningkatan angka kejadian infeksi nosocomial dirumah sakit, seperti melepaskan jam tangan atau perhiasan saat melakukan tindakan, selalu menggunakan masker dan menggunakan sarung tangan, menerapkan cuci tangan Kata Kunci: Kepemimpinan dan Healthcare Associated Infection (Hais), Covid-19